La Sostenibilidad Financiera de la Economía Popular y Solidaria medida desde los indicadores económicos del sector asociativo - Campoverde Izquierdo, Lisette Marian (2023)
Associative activities are an important space that can promote the development and competitiveness of local enterprises in the region, thanks to the process of cooperation, cost reduction and knowledge transfer. The present study aims to evaluate the financial sustainability of the associative sector of the Popular and Solidarity Economy (EPS) in the Loja canton. The data analyzed corresponds to the Loja canton period 2015-2020, the information analyzed is of longitudinal cut, the approach is quantitative because inferential statistics were used through the application of Pearson's coefficient and the contrast of Bowman's model. Type of research descriptive, since an analysis was made of the evolution of the following financial indicators: liquidity, indebtedness and profitability, and correlational to identify, within the framework of financial sustainability which variables are related to such sustainability, evaluated under the liquidity variable. Among the most outstanding results, the following are described: it was observed that there is a high indebtedness in the period analyzed, which affects the associations in terms of payment capacity; after obtaining the results of the correlations by Pearson's coefficient, it was verified that there is an inverse relationship between financial sustainability and external leverage, which leads to the conclusion that the higher the debt the sustainability of the company is affected, and finally, as a proposal to strengthen this associative system, a balanced scorecard was designed in which the results showed that this sector should focus on the financial perspective. It is concluded that the associations are considered as moderately sustainable institutions that have been and will continue to experience a growth process, being very important not only for the permanence of the Popular and Solidarity Economy, but also for the national financial system in general.